Developing an alternative medium for in-space biomanufacturing - Hakyung Lee; Jinjin Diao; Yuxin Tian; Richa Guleria; Eunseo Lee; Alexandra Smith; Millie Savage; Daniel Yeh; Luke Roberson; Mark Blenner; Yinjie J. Tang; Tae Seok Moon (Nature Communications)
Abstract In-space biomanufacturing provides a sustainable solution to facilitate long-term, self-sufficient human habitation in extraterrestrial environments. However, its dependence on Earth-supplied feedstocks renders in-space biomanufacturing economically nonviable. Here, we develop a process termed alternative feedstock-driven in-situ biomanufacturing (AF-ISM) to alleviate dependence on Earth-based resupply of feedstocks. Specifically, we investigate three alternative feedstocks (AF)—Martian and Lunar regolith, post-consumer polyethylene terephthalate, and fecal waste—to develop an alternative medium for lycopene production using Rhodococcus jostii PET strain S6 (RPET S6). Our results show that RPET S6 could directly utilize regolith simulant particles as mineral replacements, while the addition of anaerobically pretreated fecal waste synergistically supported its cell growth. Additionally, lycopene production using AF under microgravity conditions achieved levels comparable to those on Earth. Furthermore, an economic analysis shows significant lycopene production cost reductions using AF-ISM versus conventional methods. Overall, this work highlights the viability of AF-ISM for in-space biomanufacturing.